(untitled) (Materiali di Estetica. Terza serie, 2014)
«Dramas and tragedies are written about [the revolt of the son against the father], yet in reality it is material for comedy»: Deleuze and Guattari claim that the best way to reverse the Oedipus is to make it comic, instead of dramatic. The “Adventures of Doinel”, realized by François Truffaut, could be then the Oedipus comedy wished for by Deleuze and Guattari, accomplishing an anti-Oedipal revolution of the conception of desire, reversed by the productive nature of desire itself, affirmed through the mise en scène of the artistic production. KEYWORDS: Desiderio; Truffaut; Anti-edipo; Deleuze;